Effects of supplemental choline on deposition of cardiac, hepatic and abdominal fat in broiler (Bangladesh Journal of Animal Science, 2014)
Two hundred forty Hubbard Classic broiler chicks were used in a 35-day trial to study the effects of supplemental choline on deposition of cardiac, hepatic and abdominal fat in broiler. Birds were fed four types of diet: control diet without choline chloride (T0), diet containing 0.1% choline chloride (T1), 0.2% choline chloride (T2) and 0.3% choline chloride. All birds had access to feed and water ad libitum. Results indicated that, trends for deposition of cardiac, hepatic and abdominal fat was decreasing (P